2007
DOI: 10.1002/ppul.20669
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of airleak flow during humming V high‐frequency oscillatory ventilation in an open‐compartment ex‐vivo model of airleak

Abstract: High-frequency oscillatory ventilation (HFOV) using small tidal volumes and maintaining sufficient end-expiratory lung volume may be beneficial in the treatment of airleak. However, few published guidelines exist to advise clinicians on appropriate ventilator settings in this clinical scenario. The present experiment aimed to determine the effect of frequency, stroke volume (SV) and mean airway pressure (MAP) on airleak from an isolated lung model ventilated with a Humming V HFOV. We performed a crossover non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Such findings will help us to justify the need to revamp the ventilation strategies and training in Malaysia. Animal studies have shown that with appropriate ventilation strategies, pneumothorax could be reduced significantly 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…Such findings will help us to justify the need to revamp the ventilation strategies and training in Malaysia. Animal studies have shown that with appropriate ventilation strategies, pneumothorax could be reduced significantly 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…However, HFOV did not offer an advantage over protective CMV for various markers of lung injury, both in a rabbit model of lung lavage ( Rotta et al, 2001 ) or acid aspiration ( Allardet-Servent et al, 2008 ). In an ex-vivo rabbit model of air leak, both stroke volume and mPaw influenced air leak flow, but mPaw appeared to be the main independent driver of air leak ( Liu et al, 2007 ). Circuit disconnection was evaluated in a tween pig model of lung injury showing that disconnections resulted in worsening compliance and increase in FiO 2 requirement, with these effects persisting over time ( Kubiak et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%